Estimation of the direction of strokes and arpegios - Barbancho-Pérez, Isabel; Tzanetakis, George; Tardón-García, Lorenzo José; Driessen, Peter F.; Barbancho-Pérez, Ana María (My University, 2014)
Whenever a chord is played in a musical instrument, the notes are not commonly played at the same time. Actually, in some instruments, it is impossible to trigger multiple notes simultaneously. In others, the player can consciously select the order of the sequence of notes to play to create a chord. In either case, the notes in the chord can be played very fast, and they can be played from the lowest to the highest pitch note (upstroke) or from the highest to the lowest pitch note (downstroke). In this paper, we describe a system to automatically estimate the direction of strokes and arpeggios from audio recordings. The proposed system is based on the analysis of the spectrogram to identify meaningful changes. In addition to the estimation of the up or down stroke direction, the proposed method provides information about the number of notes that constitute the chord, as well as the chord playing speed. The system has been tested with four different instruments: guitar, piano, autoharp and organ.
Keywords: Música - Proceso de datos; MIR; Music Information Retrieval; Audio processing; Signal processing